Exploring the Roles of Entrepreneurial Education, Proactive Personality and Creative Self-Efficacy in the Formation of Undergraduates’ New Venture Ideas in China - Rui Hu; Caiyun Li (Behavioral Sciences, 2025)
A new venture idea is the prerequisite for discovering or building an entrepreneurial opportunity and also the foundation for undergraduates to start a new venture. Based on social cognitive theory, this paper explores the roles of entrepreneurial education, proactive personality, and creative self-efficacy in the formation of undergraduates’ new venture ideas. Using a sample of 650 undergraduates in China, we find that entrepreneurial education and proactive personality are both positively related to new venture idea formation, and proactive personalities also moderate the relationship between entrepreneurial education and new venture ideas. In addition, creative self-efficacy plays a mediating role in those direct effects mentioned above. That is, entrepreneurial education and a proactive personality can both promote the formation of undergraduates’ new venture ideas through creative self-efficacy. These results have practical significance for entrepreneurial education in universities, especially for fostering undergraduates’ creative self-efficacy.